2010
DOI: 10.1111/j.1365-3164.2009.00864.x
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopy and fungal culture of hoof horn from horses suffering from onychomycosis

Abstract: Horn samples were taken from the hooves of eight horses with clinical signs of equine onychomycosis in at least one hoof capsule. None of the horses had a documented mycological history. The predominant alterations of the horn capsules were sand cracks, white line disease, brittleness (especially around the nail holes), parakeratosis and bruising. The horn samples were stored in sterile tubes for transportation and transferred onto Sabouraud Dextrose Agar and dermatophyte test agar for mycological examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…However, aside from investigations on the diseased pododerma of the hoof (i.e. laminitis; Eps de Laat et al, 2016) and the septic components associated with white line disease (WLD; Apprich et al, 2010;Redding and O'Grady, 2012), recent research on the prevalence of and risk factors for hoof disorders in horses is scarce. Hoof disorders can cause lameness and lead to a true dysfunction of a horse, decreased welfare, economic losses for its owners and, eventually, a reduction in its durability (Lloyd and Kaneene, 1997;Floyd and Mansmann, 2007;Collins et al, 2010;Ireland et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, aside from investigations on the diseased pododerma of the hoof (i.e. laminitis; Eps de Laat et al, 2016) and the septic components associated with white line disease (WLD; Apprich et al, 2010;Redding and O'Grady, 2012), recent research on the prevalence of and risk factors for hoof disorders in horses is scarce. Hoof disorders can cause lameness and lead to a true dysfunction of a horse, decreased welfare, economic losses for its owners and, eventually, a reduction in its durability (Lloyd and Kaneene, 1997;Floyd and Mansmann, 2007;Collins et al, 2010;Ireland et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Many direct or supporting lines of evidence have indicated that possible contributors to the formation of the Gidoh include decreasing toughness of the wall based on abnormal anatomical conformation of the foot [2, 18], swelling and softening of the horny structure by water and/or urine [6,7,8,9, 19], neglect of incipient lesions relating to irregular farriery [2], and infection of the wall by microorganisms [1, 2, 4, 5, 12, 13, 15,16,17, 19]. Scientific research data have shown that keratinopathogenic fungi can invade into, and proliferate in, horny structures of the foot [1, 15, 17]. This can result in the collapse of the hoof capsule due to the production of keratolytic enzymes [1, 12].…”
mentioning
confidence: 99%
“…Scientific research data have shown that keratinopathogenic fungi can invade into, and proliferate in, horny structures of the foot [1, 15, 17]. This can result in the collapse of the hoof capsule due to the production of keratolytic enzymes [1, 12]. Regardless of many reports of bacteria within wall lesions, no report has as yet scientifically proven that the bacteria isolated from a hoof wall cavity can produce keratolytic enzymes that invade the horn and eventually disrupt the hoof wall.…”
mentioning
confidence: 99%